RAINWATER HARVESTING ANALYSIS FOR ICU BUILDING OF DR. AGOESDJAM REGIONAL GENERAL HOSPITAL, KETAPANG - Kisnadharma, Abang Gagit; Winardi, Winardi; Gunarto, Danang (Jurnal Teknik Sipil, 2024)
Clean water is indispensable for public health, especially in healthcare facilities like hospitals, which require a reliable supply to support various medical and non-medical activities. dr. Agoesdjam Regional General Hospital (RGH) in Ketapang is vital in delivering healthcare services to its community. Given challenges with traditional clean water sources, rainwater harvesting (RWH) emerges as an appealing alternative in areas lacking adequate water infrastructure.This study focuses on planning a rainwater harvesting system at dr. Agoesdjam RGH, identifying rainwater potential, designing collection and storage systems, and evaluating sustainability and effectiveness in meeting hospital water demands. The significance lies in advancing sustainable water supply systems for hospitals and guiding similar facilities toward adopting rainwater as a viable water source, enhancing healthcare service delivery and community access to clean water.The analysis shows that the daily demand for clean water for the ICU building at Dr. Agoesdjam RGH is 2.6 m ³/day, translating to 78 m ³/month based on standard guidelines. Rainfall intensity calculations (120 mm/hour) indicate a need for roof area adjustments to optimize rainwater capture. Specific gutter dimensions (8-inch horizontal, 4-inch vertical) are determined for efficient water flow. A ground tank with a volume of 135 m ³ is planned to ensure adequate water storage. This research underscores the critical role of rainwater harvesting in hospital water supply management, providing insights for effective implementation and contributing to sustainable healthcare infrastructure development.